Meir and Keeler Type Fixed Point Theorem for Set-Valued Generalized Contractions in Metrically Convex Spaces: Ladlay Khan, M. Imdad - Team, Support (Thai Journal of Mathematics, 2012)
A fixed point theorem for generalized set-valued contraction in metrically convex spaces has been proved which generalizes a fixed point theorem due to Rhoades [B.E. Rhoades, A fixed point theorem for some non-self mappings, Math. Japonica. 23 (4) (1978) 457–459]. An illustrative example is also discussed.